OPTIMIZATION DESIGN OF TOWER DOOR STRUCTURE BASED ON ISIGHT - YAN HongWen; TIAN HongQi; LV XingMei; LIANG YuGuo; OUYANG Hua (Jixie qiangdu)
In the multidisciplinary optimization ISIGHT software environment,the comprehensive application of PRO / E parametric-modeling function and ABAQUS FEA function establish a framework of CAD / CAE integrated optimization design for tower door. Firstly,the parametric geometric model of door is built,Secondly,the FEA model is established and submitted. The interaction effects and the correlation factor between the geometric parameters and stress are analyzed by the DOE method of optimal LHD algorithm. Static strength optimization design of door is done by the ASA global optimization algorithm. The whole tower weight is as objection,the can strength the optimal design solutions of the door is gotten. The paper provides a scientific design method for strength optimization design of the tower door.